Understanding continuance usage of natural gas: a theoretical model and empirical evaluation - Fernández-Guzmán, Victor (2018)
The adoption of natural gas increased notably last years, and there is some recognition that it improves the quality of life of inhabitants. While initial acceptance is an essential first step, the continued use is relevant to the long-term success of any technology. However, the literature on energy has focused on adoption and has devoted less attention to models that explain continuance usage. Accordingly, this study developed a model to explain continuance usage, grounded in Expectation-Confirmation Model (ECM). Unlike adoption models, confirmation of previous expectations and satisfaction with the experience of use have a relevant role in this phenomenon. Data was gathered through a questionnaire to 435 users of the service in a Latin American metropolis, and structural equations model was used for analysis. The results show that constructs of the ECM (perceived usefulness, disconfirmation, and satisfaction) influences on continuance intention. While the price impacts as expected, it is surprising that environmental consciousness strongly impacts the intention. These results may be useful for public agents to foster more comprehensive policies (beyond traditional: price and access), which include environmental and safety issues to consolidate the use of this energy source. Energy companies should develop strategies to manage consumer expectations and loyalty programs based on a high level of satisfaction.